Developing and Testing Informed-Consent Methods in a Study of the Elderly in Mexico - Aguila, Emma (RAND Corporation, 2015)
This report documents the process one research team developed to obtain informed consent from those choosing to participate in the research, norms and regulations for conducting research involving human subjects in the United States and Mexico, and how the team developed and tested a culturally sensitive approach for collecting informed consent among the elderly in Yucatan.